Knowledge, attitudes and practices of infection prevention and control among healthcare workers during the COVID 19 pandemic: a descriptive cross-sectional study in three Nigerian states - Bright Orji; Elizabeth Oliveras; Bartholomew Odio; Charity Anoke; Herbert Onuoha; Emmanuel Ugwa; Madeleine Howard; Ibrahim Idris; Edima Akpan; Festus Okoh; Chinyere Nwani; Oniyire Adetiloye; et al. (BMC Health Services Research, 2023)
Abstract Background Emergence of the COVID-19 pandemic created unexpected challenges for health care workers. The global and national supply chain system was disrupted, and affected infection, prevention and control (IPC) practices. This study aimed at documenting health workers knowledge, attitudes and practices (KAP) on IPC in Nigeria during the COVID-19 pandemic. Methods The descriptive, mixed-methods cross-sectional study was conducted in Ebonyi, Ondo and Niger states in October 2020. A structured questionnaire was administered to the health workers, complemented by semi-structured interviews that were audio recorded, transcribed and analyzed in Atlas.ti. Quantitative data were entered into REDCap and cleaned, transformed and analyzed using descriptive statistics in SPSS version 25.0 Findings from the qualitative interviews were used to explain the trends observed from quantitative study. Results There were demographic differences between community and facility-based health workers in our population. A greater proportion of facility-based providers reported having IPC training compared to community-based health workers ever (p < 0.01) and during the pandemic (p < 0.05). Health care workers had moderate knowledge of general IPC, and attitudes toward and practice of IPC during COVID-19 pandemic. However, the knowledge of the relative effectiveness of prevention measures was low. The mean knowledge scores were greater among facility-based workers compared to community based healthcare workers (p = 0.001). Self-reported IPC practices increased during the pandemic compared to prior to the pandemic, with the exception of the use of N-95 masks and hand sanitizer. Conclusion This study found moderate IPC knowledge, attitudes and practices in our study population during the pandemic as compared to pre-pandemic for the study found gaps in correct hand hygienevaried application of different IPC practices to ensure adherence to COVID-19 preventive measures. The study recommends sustained training for IPC and encourages policy makers that budget line specific to COVID-19 response across all the levels of health care delivery will enhance compliance and emergency readiness.